Interplay between Income Inequality and Corruption in ASEAN - Nugroho Sumarjiyanto Benedictus Maria; Mulyo Hendarto Robertus; Faiq Dhanu Robertus (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
Corruption contributes to rising income inequality by worsening access to social services, education, and economic opportunities. This study aims to examine the relationship between corruption and income inequality. Panel data was used to analyze six ASEAN countries over the period 2013-2022 with the main variables including Gini Ratio, economic growth, government spending, population, tax revenue, government effectiveness, and Corruption Perception Index (CPI). The results show that income inequality and corruption significantly affect each other. High inequality increases the risk of corruption, while corruption worsens income distribution. Other variables such as population, tax revenue, and government effectiveness also contribute to this dynamic. The study highlights the importance of effective redistribution policies and strengthened governance to reduce inequality and corruption, creating greater social and economic stability. Therefore, an integrated and complementary policy approach between reducing inequality and fighting corruption is key in creating cleaner and fairer governance.